The role of sexual versus asexual recruitment of Artemisia wudanica in transition zone habitats between interdune lowlands and active dunes in Inner Mongolia, China - Wang, Yongcui (2016)
Artemisia wudanica is an endemic, perennial pioneering psammophyte species in the sand dune ecosystems of western Horqin Sand Land in northern China. However, no studies have addressed how sexual and asexual reproduction modes of A. wudanica perform at the transitional zones between active dune inter-dune lowlands and active dunes. In early spring, quadrats were randomly set up in the study area to monitor surviving seedling and/or ramet density and frequency coming from sexual/asexual reproduction of A. wudanica. Iron sticks were inserted near each quadrat to determine wind erosion intensity (WE). Additionally, soil samples were collected nearby each quadrat to test for soil moisture (SM), organic matter (OM) and pH. Surviving seedlings of A. wudanica showed an inverse response in 15 comparison with ramets to SM, OM and WE. Soil moisture showed the most positive effect, and WE the negative effect, on surviving, sexual reproduction seedlings. Contrarily, WE had the most positive effect, and SM the negative effect, on asexual reproduction ramets. This suggests that increases in SM and decreases in WE should benefit recruitment of A. wudanica seedlings. On the contrary, ramets coming from asexual reproduction showed a different response to environmental factors in transition zone habitats. While SM was not a key constraint for the survival of seedlings, they showed a better, positive response to wind erosion environments. Overall, various study environmental parameters could be improved to foster A. wudanica invasion and settlement in the plant community through different reproductive modes, thereby promoting vegetation restoration and rehabilitation.